Peptidase inhibitors from the salivary glands of the cockroach Nauphoeta cinerea - Taranushenko, Yuliya; Vinokurov, Konstantin S; Kludkiewicz, Barbara; Kodrík, Dalibor; Sehnal, František (Insect biochemistry and molecular biology, 2009)
Inhibitory activity against subtilisin, proteinase K, chymotrypsin and trypsin was detected in the salivary glands and saliva of the cockroach Nauphoeta cinerea (Blattoptera: Blaberidae). Fractionation of the salivary glands extract by affinity chromatography followed by reverse-phase HPLC yielded five subtilisin-inhibiting peptides with molecular masses ranging from 5 to 14 kDa. N-terminal sequences and subsequently full-length cDNAs of inhibitors designated NcPIa and NcPIb were obtained. The NcPIa cDNA contains 216 nucleotides and encodes a pre-peptide of 72 amino-acid residues of which 19 make up the signal peptide. The cDNA of NcPIb consists of 240 nucleotides and yields a putative secretory peptide of 80 amino-acid residues. Mature NcPIa (5906.6 Da, 53 residues) and NcPIb (6713.3 Da, 60 residues) are structurally similar (65.4% amino acid overlap) single-domain Kazal-type peptidase inhibitors. NcPIa with Arg in P1 position and typical Kazal motif VCGSD interacted stoichiometrically (1:1) with subtilisin and was slightly less active against proteinase K. NcPIb with Leu in P1 and modified Kazal motif ICGSD had similar activity on subtilisin and no on proteinase K but was active on chymotrypsin.
Keywords: Gene Expression Regulation; sekvence aminokyselin; švábi; inhibitory proteas; Peptide Hydrolases; sekvence nukleotidů; Molecular Sequence Data; molekulární sekvence - údaje; Amino Acid Sequence; Base Sequence; Animals; Protease Inhibitors; proteasy; zvířata; regulace genové exprese; Cockroaches